Analysis of Work Motivation in Improving Employee Performance at the Makassar City Transportation Service - Andi Rahmawati Datu; Moh. Aris Pasigai; Zalkha Soraya (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the analysis of work motivation in improving employee performance at the Makassar City Transportation Service. The type of research used is interpretive qualitative research. This research was carried out at the Makassar City Transportation Service using 3 informants. The data collection techniques used in this research are observation, interviews and documentation. The research results show that work motivation plays an important role in improving employee performance, this is mainly related to fulfilling the need for a sense of security and providing rewards for employee performance achievements.